2021
DOI: 10.1071/sr20308
|View full text |Cite
|
Sign up to set email alerts
|

Impact of drying–rewetting cycles and organic amendments on phosphorus speciation of paddy soil

Abstract: Little is known about the effects of drying–rewetting cycles on phosphorus (P) speciation in paddy soils with organic amendments incorporated. In this study, the responses of microbial biomass P (MBP), alkaline phosphatase activity, inorganic pyrophosphatase activity, soluble P, available P (AP), organic P, total P (TP), organic carbon (C), and C:P ratio to two types of the organic amendment (Azolla compost and rice straw) under drying–rewetting cycles were evaluated in a 60-day incubation experiment. The expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 69 publications
2
4
1
Order By: Relevance
“…These results confirmed our first hypothesis that AWD reduced paddy soil available P content compared with CF regardless of straw addition or not. However, Bagheri et al found that AWD increased paddy soil's available P content, contrary to our results [4]. This may be due to the different soil types used in the experiment.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These results confirmed our first hypothesis that AWD reduced paddy soil available P content compared with CF regardless of straw addition or not. However, Bagheri et al found that AWD increased paddy soil's available P content, contrary to our results [4]. This may be due to the different soil types used in the experiment.…”
Section: Discussioncontrasting
confidence: 99%
“…Soil P fraction is affected by three main mechanisms: precipitation and dissolution, adsorption and desorption, and biotransformation [2]. Unlike dryland soils, the change in paddy water environment during rice production can easily affect soil P availability [3,4]. Therefore, water management in paddy plays a vital role in water use and soil nutrient availability.…”
Section: Introductionmentioning
confidence: 99%
“…After air drying under both water management systems, the available phosphorus (P) content in fresh soil increased, which aligns with the ndings of a previous study (Bagheri et al, 2021). However, the increase in available P varied between the two water management regimes at different sampling times.…”
Section: Discussionsupporting
confidence: 87%
“…It is worth noting that the effects of water management on phosphorus availability can vary depending on soil type. Studies conducted on alkaline soil have shown different results, where AWD increased the available phosphorus content (Bagheri et al, 2021). This discrepancy is likely due to the different soil conditions and pH levels.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation